Response of a non-governmental organisation to COVID-19 - Sara Varughese (Health for All Nations, 2020)
The COVID-19 pandemic has had a global impact with local or national lockdowns imposed in 172 countries. Morbidity and mortality due to the virus has seriously damaged both the health of populations and the economy. Government and non-governmental agencies (NGOs) have been hard pressed to respond meaningfully in the global crisis, the likes of which have not been experienced in recent times. A disability and development organization in India, a branch of a global non-governmental organization, reflects on the challenges and lessons learnt in responding to the crisis. The need to be alert, responsive, and consultative is highlighted.